PENGOLAHAN DATA PENJUALAN PADA MEUBEL JEPARA TEMPINO: Application, Sales Data Processing, Visual Basic 6.0, and MySQL - Rahmi, Siti; -, Afrizal (LP2M Universitas Nurdin Hamzah, 2018)
The development of computer technology is growing rapidly, not only in the educational environment but also in companies, government agencies or the private sector. The inventory data processing process is recorded quickly and accurately and efficiently. With the Sales Data Processing at the Tempo Jepara Furniture built, it is expected to maximize the processing of sales transaction data with customers. This data processing system is created using Visual Basic 6.0 tools and MySQL Database.